Kimia Medisinal dalam Terapi Kanker : Analisis Jalur Sinyal dan Interaksi Ligand-Target - Saeful Amin; Alfi Nurul Aini; Nandita Marsya Putri Utami; Dini Aryani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Cancer is a chronic disease that poses a major challenge to global health, with increasing mortality rates. Although conventional chemotherapy has been the mainstay of treatment, this approach has limitations, including non-selectivity leading to severe side effects. Therefore, the development of longer-term cancer therapies, such as targeted therapy and immunotherapy, is of great importance. Medicinal chemistry plays a role in the discovery of bioactive compounds, including xanthones from Garcinia mangostana, which exhibit anticancer activity. This article reviews the contribution of medicinal chemistry to cancer therapy through the analysis of molecular signaling pathways and ligand-target interactions, as well as the use of computational techniques in drug design. With this approach, it is expected to improve the effectiveness of therapy and the quality of life of cancer patients.